A 2ND L-TYPE ISOZYME OF POTATO GLUCAN PHOSPHORYLASE - CLONING, ANTISENSE INHIBITION AND EXPRESSION ANALYSIS - Sonnewald, Uwe; et al. (Plant Molecular Biology, 1995)
Northern analysis revealed that both forms are differentially expressed. The steady-state mRNA levels of the tuber L-type isozyme accumulates strongly in potato tubers and only weakly in leaf tissues, whereas the mRNA of the leaf L-type isozyme accumulates in both tissues to the same extent. Constitutive expression of an antisense RNA specific for the leaf L-type gene resulted in a strong reduction of starch phosphorylase L-type activity in leaf tissue, but had only sparse effects in potato tuber tissues. Determination of the leaf starch content revealed that antisense repression of the starch phosphorylase activity has no significant influence on starch accumulation in leaves of transgenic potato plants. This result indicated that different L-type genes are responsible for the starch phosphorylase activity in different tissues, but the function of the different enzymes remains unclear.
Keywords: ANTISENSE INHIBITION; DIFFERENTIAL EXPRESSION; GLUCAN PHOSPHORYLASE TYPE L; ISOZYMES; STARCH BREAKDOWN; TRANSGENIC PLANTS